Optimizing groundnut seedling growth on post-tin mining soil by adding organic growing media - Yus Dwi Yanti; Limartaida Siahaan; Mahmudin; Geby (Fakultas Pertanian Universitas Majalengka, 2025)
Soils from post-tin mining soil typically exhibit suboptimal conditions for plant growth due to low organic matter content, sandy texture, and the presence of heavy metal wastes. Groundnuts (Arachis hypogaea L.) are a highly nutritious food crop of significant economic importance, rich in protein and fat. Enhancing the quality and fertility of old tin mine soils can be accomplished by adding organic growing media to facilitate optimal groundnut cultivation. This study aims to enhance groundnut growth by the addition of organic planting media and determining of the optimal dosage. This study used a Completely Randomized Design (CRD) using organic planting media with four treatment levels: P0 = control (no organic planting media), P1 = 85% post-tin mining soil + 15% organic growing media, P2 = 75% post-tin mining soil + 25% organic growing media, P3 = 60% post-tin mining soil + 40% organic growing media. Each treatment was replicated five times, giving a total of 20 experimental units. Data were evaluated utilizing Analysis of Variance (ANOVA) succeeded by Duncan's Test at the 5% significance level. The addition of organic growing media into post-tin mining soil influenced root biomass in groundnut plants, showing a tendency to enhance leaf count and canopy biomass, however this effect was not statistically significant. This study found no significant effect on plant height.